Breastfeeding among women employed in Mexico's informal sector: strategies to overcome key barriers - Julia M. Goodman; Vania Lara-Mejía; Sonia Hernández-Cordero; Mireya Vilar-Compte (BMC, 2024)
Abstract Background Rates of exclusive breastfeeding fall below recommended levels, particularly among women in paid employment. In Mexico, more than half of women are in informal employment, meaning they lack many of the protections that may support breastfeeding. Methods In-depth interviews with 15 key informants representing government agencies (n = 6 organizations), NGOs (n = 4), international organizations (n = 2), and academia (n = 2) in Mexico. Interviews were conducted between March and June 2023. To understand and describe barriers to breastfeeding among informally employed women in Mexico according to key informants and the current and potential policies to address these barriers, we conducted a qualitative thematic analysis. Results Current policies to promote, protect, and support breastfeeding predominantly apply to all employed women, but respondents expressed concern that they did not provide adequate protection for women in informal employment. Additional themes concerned the need for relevant programs to be institutionalized and coordinated, discussions of breastfeeding as a right, and the legal equivalence (whether true in practice or not) of formal and informal workers. Conclusions Women employed in Mexico's informal sector face a dearth of maternity protections. According to key informants, few policies exist to promote, protect, and support breastfeeding among employed women, in general, but the economic vulnerability and challenging working conditions of women in informal employment exacerbates their situation. The lack of access to formal labor protections, such as paid maternity leave, creates a significant barrier to breastfeeding for women in the informal sector. Recommendations include short-term policies to fill gaps in social protection for informally employed women, as well as longer-term solutions such as the development of universal social protection programs and supporting formalization.